The Interferon-Induced Exonuclease ISG20 Exerts Antiviral Activity through Upregulation of Type I Interferon Response Proteins - Christopher M. Weiss; Derek W. Trobaugh; Chengqun Sun; Tiffany M. Lucas; Michael S. Diamond; Kate D. Ryman; William B. Klimstra (mSphere, 2018)
ABSTRACT Type I interferon (IFN)-stimulated genes (ISGs) have critical roles in inhibiting virus replication and dissemination. Despite advances in understanding the molecular basis of ISG restriction, the antiviral mechanisms of many remain unclear. The 20-kDa ISG ISG20 is a nuclear 3′–5′ exonuclease with preference for single-stranded RNA (ssRNA) and has been implicated in the IFN-mediated restriction of several RNA viruses. Although the exonuclease activity of ISG20 has been shown to degrade viral RNA in vitro, evidence has yet to be presented that virus inhibition in cells requires this activity. Here, we utilized a combination of an inducible, ectopic expression system and newly generated Isg20−/− mice to investigate mechanisms and consequences of ISG20-mediated restriction. Ectopically expressed ISG20 localized primarily to Cajal bodies in the nucleus and restricted replication of chikungunya and Venezuelan equine encephalitis viruses. Although restriction by ISG20 was associated with inhibition of translation of infecting genomic RNA, degradation of viral RNAs was not observed. Instead, translation inhibition of viral RNA was associated with ISG20-induced upregulation of over 100 other genes, many of which encode known antiviral effectors. ISG20 modulated the production of IFIT1, an ISG that suppresses translation of alphavirus RNAs. Consistent with this observation, the pathogenicity of IFIT1-sensitive alphaviruses was increased in Isg20−/− mice compared to that of wild-type viruses but not in cells ectopically expressing ISG20. Our findings establish an indirect role for ISG20 in the early restriction of RNA virus replication by regulating expression of other ISGs that inhibit translation and possibly other activities in the replication cycle. IMPORTANCE The host immune responses to infection lead to the production of type I interferon (IFN), and the upregulation of interferon-stimulated genes (ISGs) reduces virus replication and virus dissemination within a host. Ectopic expression of the interferon-induced 20-kDa exonuclease ISG20 suppressed replication of chikungunya virus and Venezuelan equine encephalitis virus, two mosquito-vectored RNA alphaviruses. Since the replication of alphavirus genomes occurs exclusively in the cytoplasm, the mechanism of nucleus-localized ISG20 inhibition of replication is unclear. In this study, we determined that ISG20 acts as a master regulator of over 100 genes, many of which are ISGs. Specifically, ISG20 upregulated IFIT1 genes and inhibited translation of the alphavirus genome. Furthermore, IFIT1-sensitive alphavirus replication was increased in Isg20−/− mice compared to the replication of wild-type viruses but not in cells ectopically expressing ISG20. We propose that ISG20 acts as an indirect regulator of RNA virus replication in the cytoplasm through the upregulation of many other ISGs.